Acute exacerbation impairs endothelial function in patients with chronic obstructive pulmonary disease - (:unkn) unknown (My University, 2010)
OBJECTIVES: The effect of acute exacerbation of chronic obstructive pulmonary disease (COPD) on brachial artery flow-mediated dilation (FMD) has not been examined. The aim of this study was to assess the endothelial function of COPD patients during acute exacerbations. STUDY DESIGN: The study included 30 consecutive patients (8 women, 22 men; mean age 64.2+/-10.9 years) who experienced acute exacerbation of COPD, defined according to the Anthonisen criteria (increased dyspnea, sputum, and sputum purulence). All patients received the same antibiotic and bronchodilator treatment. Endothelial function was assessed by brachial artery ultrasonography within the first 48 hours and after complete resolution of exacerbation symptoms. Flow-mediated dilation was defined as both the maximum absolute and maximum percentage changes in the vessel diameter during reactive hyperemia. The results were compared with those of 20 age-and sex-matched controls without COPD. RESULTS: The patient and control groups were similar in terms of age, gender, hypertension, diabetes, hyperlipidemia, coronary artery disease, heart rate, and blood pressure. Parameters of FMD during acute exacerbation were significantly lower than those obtained after recovery (absolute change: 0.23+/-0.12 mm vs. 0.38+/-0.17 mm, p<0.001; percentage change: 6.44+/-3.99% vs. 10.42+/-4.86%, p<0.001) and than those of the control group (absolute change: 0.36+/-0.13 mm, p=0.001; percentage change: 9.77+/-3.83%, p=0.003). Flow-mediated dilation increased significantly after recovery, yielding similar values to those of the controls. Improvements in FMD were significant in both sexes. CONCLUSION: Acute COPD exacerbation is associated with worsening endothelial function, increasing the risk for cardiovascular morbidity.
Keywords: Female; Humans; Middle Aged; Aged; Ultrasonography; Male; Reference Values; Disease Progression; Endothelium, Vascular; Brachial Artery; Blood Flow Velocity; Forced Expiratory Volume; Vasodilation; Vital Capacity; Pulmonary Disease, Chronic Obstructive